Memory of the grassland: how to keep singing Mongolian Gur songs in today’s Ordos City, China - Ruiping, Wu; Wei, Chow Ow (Logos Verlag Berlin, 2024)
Ordos is a prefecture-level city of the Inner Mongolia Autonomous Region. Besides the famous Genghis Khan’s Remembrance Place2 as its significant feature of the past, it also features some gür songs of the Mongolian grassland. Although little known to the world, gür songs have long served in Mongolian rulers’ circles from ancient times. Through reconstruction, revitalization, and re-textualization over three millennia, gür songs are regarded to represent the local Mongolian culture, as they are deeply rooted in Hangin (a special district of the city) of Ordos. Crises of a heritage solely built on a single inheritor are emerging: Will the cultural memory of the community decay after the demise of the ‘inheritor’? Will there be a memory gap? Does the orally transmitted ritual music preserve the cultural memory of the Mongolian community in the process? How does the century-old music tradition find its connection to Ordos, a city with an urbanization history of less than 20 years? This discussion queries the reconstitution of memory through an ethnography of this Mongolian heritage example in Ordos, expecting it to be a critical inspection for the persistence of the cultural memory of the community.